2000
DOI: 10.1101/gr.138000
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Potential Tumor Markers and Antigens by Database Mining and Rapid Expression Screening

Abstract: Genes expressed specifically in malignant tissue may have potential as therapeutic targets but have been difficult to locate for most cancers. The information hidden within certain public databases can reveal RNA transcripts specifically expressed in transformed tissue. To be useful, database information must be verified and a more complete pattern of tissue expression must be demonstrated. We tested database mining plus rapid screening by fluorescent-PCR expression comparison (F-PEC) as an approach to locate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…Proteomic technologies have been used to identify cancer-specific proteins that are useful for cancer diagnosis, progression, and therapeutic targets (Wilkins et al, 1996;Loging et al, 2000;Pandey and Mann, 2000). The objective of present study was to identify cancer-associated proteins using a proteomic approach by analyzing protein expression in healthy and cancerous stomach tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic technologies have been used to identify cancer-specific proteins that are useful for cancer diagnosis, progression, and therapeutic targets (Wilkins et al, 1996;Loging et al, 2000;Pandey and Mann, 2000). The objective of present study was to identify cancer-associated proteins using a proteomic approach by analyzing protein expression in healthy and cancerous stomach tissues.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the mortality and improve the effectiveness of therapy, many studies have tried to find key biomarkers. Biomarkers are important molecular signposts of the biologic state of a cell at a specific condition (Tahara et al, 1996;Loging et al, 2000). Two-dimensional gel electrophoresis (2-DE) is widely used for in investigation of protein complements between diseased and healthy tissue with the purpose of developing diagnostic markers and detecting novel drug targets (Wilkins et al, 1996;Gygi et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is able to induce an intermediate stage of cellular adhesion with ablation of focal adhesions, to regulate matrix deposition and to induce growth inhibition in different cancer cells (Murphy-Ullrich et al, 1995;Bradshaw and Sage, 2001;Framson and Sage, 2004). In addition to its physiological role, SPARC has been linked to cancer progression as many cancer types present increased levels of SPARC expression upon invasion or metastasis (Rempel et al, 1998;Loging et al, 2000;Bradshaw and Sage, 2001;Framson and Sage, 2004). SPARC is highly expressed in a wide range of human malignant neoplasms, and the deregulated expression of SPARC is often correlated with disease progression and/or poor prognosis (Bellahcene and Castronovo, 1995;Porte et al, 1995Porte et al, , 1998Porter et al, 1995;Massi et al, 1999;Yamanaka et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies in vivo have demonstrated that the pattern of ANXA1 expression in human cancer is not well defined. While up-regulation of ANXA1 was previously observed in glioblastoma 14 and mammary adenocarcinoma, 15 many investigators have reported that ANXA1 expression was reduced or lost in other cancer tissues. Down-regulation of ANXA1 was reported in many types of cancers, including in head and neck, 8,10 esophageal, 10 gastric, 16 prostate 10,12 and breast.…”
mentioning
confidence: 97%